Adsorptive desulphurization study of liquid fuels using Tin (Sn) impregnated activated charcoal - Shah, Syed Sikandar [UNESP]; Ahmad, Imtiaz; Ahmad, Waqas (Elsevier, 2016)
Keeping in view the growing concern regarding desulphurization of petroleum products, the present study was under taken to investigate the efficiency of tin impregnated activated charcoal (Sn-AC) as a potential adsorbent for the desulphurization of model and real commercial straight run kerosene and diesel oil samples. The adsorbent Sn-AC was prepared by wet impregnation process in the laboratory and characterized by SEM, EDX and surface area analysis. Initial experiments were carried out using model oil, which was prepared by dissolving dibenzothiophene (DBT) in cyclohexane, the optimum conditions for desulfurization were found to be, 60 °C temperature, 1 h contact time and adsorbent dosage of 0.8 g, under which about 99.4% of DBT removal was attained. Under optimized conditions the desulfurization of real oil i.e., kerosene and diesel oil was also investigated. Kinetic studies revealed that DBT adsorption followed pseudo second order kinetics and the data best fits in the Langmuir adsorption isotherm as compared to Freundlich adsorption isotherm model. The adsorbent could be easily regenerated simply by washing with toluene for a multiple cycles and reused without losing its efficiency.
Keywords: Activated charcoal; Adsorption; Dibenzothiophene (DBT); Diesel oil; Regeneration